2009
DOI: 10.1007/s11661-009-9980-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Slip Morphology and Fatigue Crack Initiation in Surface Grains of Ni200

Abstract: The evolution of slipbands into fatigue cracks in surface grains of commercially pure Ni, in wt pct), was studied at ambient temperature. Round-bar specimens with electropolished surfaces were fatigued under displacement-controlled, fully reversed conditions at four strain amplitudes under a nominal strain rate of 1 9 10 À3 s À1 . Low-cycle fatigue tests were periodically interrupted to characterize the slip morphology at various fatigue cycles using scanning electron microscopy. The results showed that the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 19 publications
0
11
0
4
Order By: Relevance
“…Besides evaluating the defect location tending to a crack based on stress concentration factor, a theoretical model to determine the crack nucleation lifetime was proposed by introducing the stress concentration factor due to defects []KtnormalΔσ()1r*ρnormalΔσeNiα=ζ where K t is the stress concentration factor of defects, Δ σ is the applied stress range, r * is the distance ahead of pores dominated by crack initiation, ρ is the local radius of pores, Δ σ e is the endurance limit, N i is the crack initiation life, α is the fatigue life exponent, and ζ is the fatigue life coefficient.…”
Section: Experiments and Simulationsmentioning
confidence: 99%
“…Besides evaluating the defect location tending to a crack based on stress concentration factor, a theoretical model to determine the crack nucleation lifetime was proposed by introducing the stress concentration factor due to defects []KtnormalΔσ()1r*ρnormalΔσeNiα=ζ where K t is the stress concentration factor of defects, Δ σ is the applied stress range, r * is the distance ahead of pores dominated by crack initiation, ρ is the local radius of pores, Δ σ e is the endurance limit, N i is the crack initiation life, α is the fatigue life exponent, and ζ is the fatigue life coefficient.…”
Section: Experiments and Simulationsmentioning
confidence: 99%
“…[37] However, there are indeed major differences in the surface slip band development between the present alloy and those planar slip alloys such as 70Cu-30Zn alpha brass, [36] Cu-16 at. pct Al alloy, [37] Ni200, [41] and Zircaloy-2 alloy. [42] One of the new and significant findings of this investigation is that only limited slip bands were developed even in samples cycled at high stress levels with large cycling numbers; whereas for those typical planar slip materials, the number of slip bands would keep increasing with further cycling and sometimes they would cover the entire gage surface.…”
Section: B Planar-slip Deformation Mode and Strain Localization Behamentioning
confidence: 99%
“…[42] One of the new and significant findings of this investigation is that only limited slip bands were developed even in samples cycled at high stress levels with large cycling numbers; whereas for those typical planar slip materials, the number of slip bands would keep increasing with further cycling and sometimes they would cover the entire gage surface. In fact, Chan et al [41] reported that in Ni200, some surface grains were deformed severely and exhibited a rough surface topography due to the formation of extrusions and slip steps of planar slip bands, while some surface grains showed the absence of slip lines with no evidence of plastic deformation. This behavior is very similar to the present alloy.…”
Section: B Planar-slip Deformation Mode and Strain Localization Behamentioning
confidence: 99%
“…Em pesquisa de Huang e Ren (1991), foi observado o surgimento de micro trincas nesses microentalhes em amostras da liga GH33A, além de observarem, que a rugosidade e o endurecimento da superfície provocam uma deformação localizada, sendo este o principal fator que diminui a vida em fadiga de baixo ciclo. No entanto, a tensão residual e também a rugosidade foram apontadas como principais agentes para diminuir a vida em fadiga de alto ciclo.…”
Section: Características Que Influenciam No Comportamento Em Fadigaunclassified
“…Estes deslizamentos são representados através de linhas paralelas que se movimentam quando os materiais sofrem tanto o carregamento cíclico quanto monotônico. As irregularidades provocadas pelas intrusões formam concentradores de tensão e as extrusões, são responsáveis pela rugosidade da superfície dos grãos, figura 2.3 (Chan et al 2009;Stephens et al 2001).…”
Section: Características Que Influenciam No Comportamento Em Fadigaunclassified